2018
DOI: 10.18203/2320-1770.ijrcog20184155
|View full text |Cite
|
Sign up to set email alerts
|

Study of correlation of ultrasonography with surgical evaluation of adnexal masses: a prospective study

Abstract: Background: Adnexal masses are one of the most common pathologies among women of all age groups. Ovarian tumors, alone, represent two thirds of these cases. Malignant ovarian tumors are the fourth most common cause of death in women. Accurate diagnosis is required foremost for proper treatment and management of the patients.Methods: A prospective study done on 100 patients with adnexal masses presenting to Department of Obstetrics and Gynecology at Kamla Raja Hospital, G.R.M.C, Gwalior from February 2015 to Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…Seemer et al 12 observed tubal pathology in 33.33% cases, ovarian pathology in 60% cases and 6.66% showed combined pathology. However our findings are in discordance with Tripathi et al 13 who studied 100 cases of adnexal masses and found 56% of cases were ectopic gestation, 10% were ovarian in origin, 31% had a dual origin while 3% cases were found originating from the broad ligament.…”
Section: Discussioncontrasting
confidence: 99%
“…Seemer et al 12 observed tubal pathology in 33.33% cases, ovarian pathology in 60% cases and 6.66% showed combined pathology. However our findings are in discordance with Tripathi et al 13 who studied 100 cases of adnexal masses and found 56% of cases were ectopic gestation, 10% were ovarian in origin, 31% had a dual origin while 3% cases were found originating from the broad ligament.…”
Section: Discussioncontrasting
confidence: 99%